BAGAIMANA PERTUMBUHAN EKONOMI MENJADI BIAYA: PENGGANDA KELANGKAAN - Lasmiatun - (DHARMA EKONOMI, 2011)
Competent macro-accocation of natural capital would allow micro-allocation by economics to be fully useful and may help prevent the latter being confused with the former. This macro-accocation requires social choice, so to see whether it is likely to be competent the effectiveness of democratic politics is investigated. Dysfungtion is predicted becauise democratic institutions produce elements of irresponsibility and ignorance, the permit inflation of want by supply (IWS) a possitive feedback in which wants are increased by their supply, provoking more supply, hence more want. Four IWS systems combine under common conditions to indefinitely escalate the scarcity of natural capital, a critical failure of macro-allocation. This scarcity multiplier couses apparentty rational attempts to satisfy a few wants to exacerbate many, increasing dissatisfaction. Institution for deliberative public participation may enable democraticies to recognize and control IWS. Unless this is done the scarcity multiflier may make cost-benefit analysis mistending : it may make the costsof development project exceed their benefits in proportion to their financial succes.Keywords : natural capital, population, contingency of preference, cost-benefitt  analisis, macro - allocation